Optimized Design of Polyethylene Fiber-Engineered Cementitious Composite Mix Ratio Based on the Analytic Hierarchy Process - Fengxia Han; Qing Liu; Xin Guo; Yanfeng Niu (Advances in Materials Science and Engineering)
Finding a method to optimize the design of the polyethylene fiber-engineered cementitious composite (PE-ECC) mix proportion is an urgent endeavor. The analytic hierarchy process (AHP) is an efficient decision-making tool for complicated problems with multiple variables and uncertainties. In this study, initial cracking strength, ultimate tensile strength, tensile displacement, and test age, as influencing factors of the PE-ECC optimum mix design were considered. The weightings of the factors were quantified through the AHP method according to the tensile test results of 14 groups of specimens with different mix proportions. The water to binder ratios (0.25, 0.27, 0.29, 0.31), the mineral admixtures (30%, 40%, 50%, and 60%), and the PE ratio (2%) were the three main test parameters for the factors of the PE-ECC tensile properties. The weight of each influence factor was calculated by constructing a matrix, which confirmed that the judgment matrix satisfies the consistency test. The optimum mixture ratio of 30% fly ash and 0.27 water-binder ratio were obtained. The results demonstrate the applicability and rationality of the AHP theory. The findings from this study can be used as a guideline for the optimized design of PE-ECC mix proportions.